Pendampingan Optimalisasi Digital Marketing Memanfaatkan Social Media - Cahyono, Nuri (Jurnal Ilmiah Pengabdian dan Inovasi, 2022)
Digital marketing is the spearhead that determines how a business is able to grow or just run as it is and even experience a decline. By entering the mataverse era, one of the main choices for digital marketing media is social media. Social media is able to provide comprehensive promotions and reach the online marketing area broadly, specifically to personal as users of the social media. This has become the choice of one of the non-formal educational institutions in Yogyakarta, namely kampung inggris yogyakarta, which has begun to enter promotions by utilizing social media, mainly Instagram, both with organic methods and ads. In the implementation of this community service, assistance is carried out to provide knowledge for partners so that they will be able to later independently implement digital marketing based on social media. The initial stage is to insert a media to accommodate information that can be used as a reference, namely a website. Next, an advertisement using Facebook ads is carried out with a target Instagram user, this ad is carried out in 3 periods or about 3 months with an evaluation applied every month.